Influence of Online and Physical Classrooms on Students Academic Performance - Ebenezer Omolafe Babalola; Samuel Adenubi Onasanya (Indonesian Journal of Multidiciplinary Research, 2024)
This study investigated the influence of online and physical classrooms on student academic performance. The descriptive research of the survey type was employed for the target population for the study consisting of 200 students in five randomly selected faculties at the University of Ilorin, Nigeria. The findings of this study were that both online and physical learning positively influenced students’ academic performance; students faced challenges while learning both physically and virtually; students engaged online performed better than those engaged physically with a mean difference of 2.38; there was a significant difference between the academic performance of students taught in an online classroom based on faculty; and there was no significant difference between the academic performance of students taught in an online class based on gender. It was concluded that physical and online education have many things in common. Students must still turn in assignments, participate in class, understand the content, and finish group projects. Teachers still need to create lesson plans, improve the quality of their teaching, respond to students' queries in class, encourage learning, and grade assignments.